MENINGKATKAN KEMANDIRIAN BELAJAR DAN HASIL BELAJAR MATEMATIKA SISWA SMP DENGAN MENGGUNAKAN PENDEKATAN SAINTIFIK PADA MASA PANDEMI COVID-19 (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This research is a type of classroom action research that aims to examine the improvement of independence learning and the results of mathematics learning of junior high school students on the  transformation material. The scientific approach is used as one of the learning approaches so that there is an increase in student independence learning and the results of students' math learning. This research was conducted at  MTS Negeri Cimahi involving 31 students. The research implementation was designed in two cycles consisting of cycle I and cycle II. Each cycle is carried out in 2 meetings each. The results of this study indicate an increase in students' learning independence and the results of students' math learning , as seen in the first and second cycle tests, there is an increase in independence learning and the results of students' math learning. Therefore, scientific approaches can be used in mathematics learning conducted online during the Covid-19 pandemic.